Análisis de las figuras retóricas usadas en el segmento deporte del Diario El Universo, en el primer trimestre del 2019 - León Muñoz, Diana Yazmín (2020)
Rhetorical figures are a form of communication through phrases or striking words used to give a sense of originality to the message you want to convey. In recent years, sports journalism has implemented these literary expressions in its newsrooms in order to generate a higher level of attention in its readers. In this research study, we intend to analyze the use of rhetoric used by El Universo newspaper in its editions of the months of January, February and March of the previous year, using a qualitative method based on non-participant observation and exploratory research techniques that they will help to gather information; also the observation sheets that will be applied in order to structure the data and perform a complete analysis. After having performed the respective analysis it was found that the literary phrases are more applied in the headlines of the sports notes of the newspaper, because it is the first thing consumers see in this newspaper. Rhetoric is a fundamental part of the communication, therefore, journalists will use it continuously because of the reception they receive among the followers of this news field.